Analisis Penerapan Manajemen Risiko Keselamatan dan Kesehatan Kerja (K3) di Rumah Sakit X Jakarta Tahun 2025 - Albert Hasibuan; I.Gusti Ngurah.Y.Usdayana; Anita Sriwaty Pardede (Jurnal Rumpun Ilmu Kesehatan, 2026)
Risk management is a preventive measure for service-sector companies, particularly hospitals, which are vulnerable to errors and complaints. Mapping risks according to work units is essential to minimize accidents or errors affecting patients, visitors, and staff. This study aims to examine and identify the implementation of Occupational Health and Safety (OHS) risk management at Hospital X in Jakarta. A quantitative cross-sectional design was employed to describe OHS risk management implementation across units and workplaces by identifying risks, analyzing hazards, and determining appropriate control measures. The study examined hazards that could cause accidents among employees, visitors, and patients, as well as efforts to minimize incidents and accidents. Statistical analysis showed that all examined variables significantly influenced OHS risk management implementation in 2025. The p-values were 0.028 for Knowledge, 0.001 for Attitude, 0.000 for Practice/Behavior, 0.000 for Organizational Structure and Management Support, 0.018 for Risk Identification and Assessment, and 0.009 for Training, Competence, and Preparedness. All variables had p-values ≤ 0.05. The study concludes that Knowledge, Attitude, Practice/Behavior, Organizational Structure and Management Support, Risk Identification and Assessment, and Training, Competence, and Preparedness significantly influence OHS risk management implementation at Hospital X in 2025.